பூசலார்நாயனாரின் பத்தியில் சீர்மிகு சிந்தனை (FASCINATING THOUGHT IN THE BHAKTI OF THE POOSALANAYANAR) - C., Mohan Kumar (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2018)
In order to have a cult-rich and ethical way of life, it is better to adopt an ethical way of life. Worship that is neither dull nor dull is important to us. The Poosalar did not worry that the temple was not meant to be built. He claimed that the best place of worship is the mind; he worshiped as such of new cult itself. His grandiloquence shook the Lord. Our position, our education and the question are not great in sense. The house of the Lord is the mental realization. The Lord is not bound to like and dislike; he is a neutral realist; he is not a solicitor; he dislikes fakes. Therefore, it is important that we learn to adopt a simpler way of life. True worship is to be praised and worthy of praised. The Poosalar offer us a new path of life, the beneficiaries that would guide us to become better human. In view of them, it is good to feel the greatness of the Poosalar that the Lord will accept the simplicity. This article explores his preaching that open a high path for mankind, who is so busy seeking fortune in the materialized world. செறிவான வழிபாடும் வாழ்வியல் நெறிமுறையும் வேண்டுமெனில், தகைமேவிய நலஞ்சார் பண்பியல்பு வேண்டுவது நன்று. மங்கலோ மழுங்கலோ கிஞ்சீற்றுமில்லாத வழிபாடு நமக்கு முக்கியம். ஆலயம் எழுப்ப பொருள் இல்லையே என்று பூசலார் துயரம் கொள்ளவில்லை. மனத்தினையே இடமாகக் கொண்டுசெய்த வழிபாட்டு நெறிமுறையால் உலகுக்குப் புதுவழியைக் காட்டியவர் பூசலார். அவர் மேற்கொண்ட அகவழிபாடு இறைவரையே அசைக்கின்றது. நம் பதவியும் பகட்டும், கல்வியும் கேள்வியும் பெரிதல்ல. உளமார்ந்த மெய்வழிபாடே இறைவர் இருக்கும் வீடு. இறைவர் விருப்பு வெறுப்பு அற்றவர்; நடுநிலையான மெய்யினர்; அவர் வேண்டுதல் வேண்டாமையாளர்; போலிகளை விரும்பார். எனவே, எளிமையான அகவழிபாட்டும் முறையையும் சைவசமயம் முன்னெடுப்பதை நாம் கற்றுத் தெளிவது அவசியம். உண்மை வழிபாடென்பது பகட்டுக்கும், புகழுக்கும் செய்வதன்று. வாழ்க்கை உயர்நெறியில் பயணப்பட்டு, நயன்மைப்பெற்று உய்யவே அருளார்கள் நமக்கு வழிகாட்டுகின்றனர். அவற்றைக் கருத்திலேற்றி, எளிமையையும் இறைவர் விரும்பி ஏற்பார் என்ற பூசலார் காட்டும் பெருநெறியை உள்ளார்ந்து உணரக்கடவது மாண்பாகும்.